A novel and expeditious synthesis of oxazolidinone drugs linezolid and eperezolid - Siddaraj, Ranjith; Govindaiah, Shivaraja; Ningegowda, Raghu; Shivananju, Nanjunda Swamy; Priya, Babu Shubha (European Journal of Chemistry, 2018)
A concise and efficient synthesis of linezolid and eperezolid were accomplished through a convergent scheme utilizing diverse reaction conditions. The synthesis demonstrates utility of a new approach to facilitate the expeditious construction of 3-aryl-5-(substituted methyl)-2-oxazolidinones and easier insertion of N-acetyl group. This new approach offers the possibility of accessing related 2-oxazolidinone members easily as well as making additional analogues of Linezolid. The adopted method afforded high purity and excellent yield compared to other existing synthetic methods. The compounds were successfully characterized by known spectroscopic techniques.